IFPRI Malawi Monthly Maize Market Report, May 2025 - International Food Policy Research Institute; Benson, Anderson (International Food Policy Research Institute, 2025)
Highlights Retail prices of maize bottomed out in May. Prices rose in southern Malawi despite continued imports. Maize retailed below the government-mandated price in 25 out of 26 monitored markets.